Dialling Up Resilience Stakeholder Consultation Workshop - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
A consortium of partners led by the Overseas Development Institute (ODI) held a stakeholder consultative workshop on 6 July 2015 at the International Livestock Research Institute (ILRI) in Nairobi, Kenya, to solicit input into a proposal on measuring resilience in the Horn of Africa. The proposal, named “Dialling Up Resilience”, is in response to a call for initiatives by the Global Resilience Partnership, a joint partnership between the Rockefeller Foundation, USAID, and Sida to find new solutions to improve lives in Africa and Asia. Forty people attended the stakeholder workshop and provided insight into existing resilience measurement initiatives, key players in the arena, and barriers and incentives to improving standardization and quality of resilience measurement. The attendees represented two dozen organizations across government, NGOs, and civil society, working in the Horn of Africa and beyond. While all the attendees are equally committed to increasing the resilience of individuals and communities in Kenya (and beyond), we all also approach this challenge from a myriad of perspectives. Rather than seeing this as a difficulty to overcome, the workshop participants embraced the many available paths as different yet complementary approaches will be necessary in different places and with different people. The consortium’s desire with Dialling Up Resilience is to support these various campaigns in analysing their effectiveness, self-improvement, and use of mechanisms to involve the target populations. The workshop led to shifts and tweaks to the Solution Statement submitted to the Global Resilience Partnership. These changes were based on adapting to the needs and suggestions of participants, to whom we are indebted for bringing their long experience to bear on a complex and long-standing challenge, and with whom we hope to collaborate if the next stage of the program is accepted.